Analisis Maqashid Shariah Terhadap Implementasi Zakat Digital pada BAZNAS - Khusnudin; Muhammad Iqbal Fatoni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Zakat is a commandment of Islamic law to create social justice. In this modern era, zakat has turned digital to facilitate the givers and recipients of zakat. Maqashid sharia becomes one of the guidelines for implementing an order from the founder of the sharia. Badan Amil Zakat Nasional is one of the government-owned institutions that manages zakat. So, the role of Baznas becomes very important in creating social justice in accordance with maqashid sharia. The purpose of this research is to see the implementation of maqashid shariah in digital zakat at the National Amil Zakat Agency, as well as how Baznas implements digital zakat and its potential in the future. This research uses a qualitative approach method and looks at existing facts and data. The results of the research can be a guideline for other zakat management institutions to create social justice in accordance with maqashid sharia as done by the National Amil Zakat Agency.